2015
DOI: 10.5194/isprsarchives-xl-1-w5-631-2015
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Allocation of Water to the Cultivation Farms Using Genetic Algorithm

Abstract: ABSTRACT:The water scarcity crises in the world and specifically in Iran, requires the proper management of this valuable resource. According to the official reports, around 90 percent of the water in Iran is used for agriculture. Therefore, the adequate management and usage of water in this section can help significantly to overcome the above crises. The most important aspect of agricultural water management is related to the irrigation planning, which is basically an allocation problem. The proper allocation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Selection of proper measures for the evaluation of clustering algorithms depends on the available information and utilized methods [42,43]. Two types of evaluation measures have been used in the literature: internal indices and external indices.…”
Section: Quality Measuresmentioning
confidence: 99%
“…Selection of proper measures for the evaluation of clustering algorithms depends on the available information and utilized methods [42,43]. Two types of evaluation measures have been used in the literature: internal indices and external indices.…”
Section: Quality Measuresmentioning
confidence: 99%
“…They have the ability to solve complex optimization problems in wide and many-dimensional search spaces. Artificial intelligence techniques are widely used and considered in many computing research [14,15]. In a paper by Yi and Kumar [16], provision of the facilities is divided into two phases of determining the vehicle routes and dispatching the relief commodity, which are optimized using the ACO algorithm.…”
Section: Meta-heuristic Algorithmsmentioning
confidence: 99%
“…Among these methods are meta-heuristic algorithms. Meta-heuristic algorithms have been used in different engineering and management issues [15]. Also, studies in CRM showed that meta-heuristic algorithms increase clustering quality.…”
Section: Introductionmentioning
confidence: 99%